THE UTILIZATION OF THE STORY OF BATU MENANGIS IN FOSTERING NOBLE CHARACTER IN GRADE 4 STUDENTS OF PUBLIC SCHOOL 7 MUARA TELANG - Alfina Sundari; Aswadi Jaya; Mega Prasrihamni (Universitas PGRI Palembang, 2025)
The purpose of this study was to describe the benefits of crying stone stories in fostering noble character in 4th grade students of SD Negeri 7 Muara Telang. The research method used is descriptive qualitative research method. Data collection techniques are observation, interview, and documentation. The results in this study indicate that students already know the benefits of crying stone stories and implement noble actions in their daily lives and understand the utilization of crying stone stories in fostering noble character. The conclusion that most students can understand the benefits and moral messages in the story well can be proven by increasing students' insight into noble character and significant changes in student attitudes both that it is found that students already know the benefits of crying stone stories and implement noble actions in everyday life and understand the utilization of crying stone stories in fostering noble character.